ChemInform Abstract: [RuCl2(p‐Cymene)]2‐Catalyzed Conjugate Addition of Arylboronic Acids to α, β‐Unsaturated Ketones under Ligand‐Free and Neutral Conditions. Issue 33 (25th July 2013) - Zhang, Lei; Xie, Xiaomin; Fu, Lei; Zhang, Zhaoguo
Abstract A simple and efficient ruthenium‐catalyzed reaction for the synthesis of various substituted ketones is presented.